Hyper-arousal vitality and its repair for attention deficit hyperactivity disorder - Chen, Deqiao; Zhao, Zhu; Chen, Wei (Frontiers in Psychiatry, 2026)
Although the social challenges faced by individuals with attention deficit hyperactivity disorder (ADHD) are often attributed to attention deficits and hyperactive symptoms, their complexity necessitates re-examination from the perspective of dynamic vitality forms (VFs). VFs theory emphasizes the central role of dynamic movement styles (e.g., intensity, rhythm, spatiotemporal trajectories) in emotional transmission and intention understanding during social interactions. This study integrates neural mechanisms and behavioral characteristics to explore the abnormal manifestations of VFs in ADHD and determine their impact on social interactions. Individuals with ADHD exhibit significant dysregulation in the stability, intensity, coordination, and emotional valence of VFs, which is associated with functional abnormalities in the dorsal central insula-middle cingulate cortex (DCI–MCC) circuit that involve dopamine system dysregulation, motor coordination deficits, and emotional integration imbalances. Leveraging the dynamic plasticity of VFs, this study proposes intervention pathways such as structured motor training, impulse control, and VFs mirroring exercises to improve social functioning by utilizing the cognitive flexibility advantages of ADHD. It underscores the importance of addressing the social challenges of ADHD by moving beyond traditional behavioral frameworks and focusing on the dynamic repair of VFs.